2016
DOI: 10.1038/srep30332
|View full text |Cite
|
Sign up to set email alerts
|

Determination of oxygen extraction fraction using magnetic resonance imaging in canine models with internal carotid artery occlusion

Abstract: Perfusion of the penumbra tissue below the flow threshold for functional disturbance but above that for the maintenance of morphological integrity is the target for therapy in acute ischaemic stroke. The measurement of the oxygen extraction fraction (OEF) may provide a direct assessment of tissue viability, so that irreversible tissue damage and penumbra can be reliably identified. By using an asymmetric spin echo single-shot echo planar imaging (ASE-SSEPI) sequence, the quantitative OEF was obtained in the is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
6
1
Order By: Relevance
“…On the other hand, CBF values in the current case report are lower compared to other reports where dynamic susceptibility contrast‐enhanced PWI technique was used . Although CBF is an absolute value, the CBF measurement method could have an influence, as our acquired values were most similar to the values obtained in the study where pCASL method was also used . Second, different anesthesia protocols could have led to these discrepancies …”
Section: Discussioncontrasting
confidence: 48%
“…On the other hand, CBF values in the current case report are lower compared to other reports where dynamic susceptibility contrast‐enhanced PWI technique was used . Although CBF is an absolute value, the CBF measurement method could have an influence, as our acquired values were most similar to the values obtained in the study where pCASL method was also used . Second, different anesthesia protocols could have led to these discrepancies …”
Section: Discussioncontrasting
confidence: 48%
“…Furthermore, a recent T2' imaging study in canine models of stroke found that OEF pathophysiology is markedly different between the infarct core, ischemic penumbra, and benign tissues as identified on histology. 57 Because we were limited to vessels of sufficient caliber to avoid partial volume effects, oxygenation values in the infarcted hemisphere may reflect a combination of penumbra and benign oligemia, which cannot be differentiated on DSC MRI. This effect may have diluted OEF differences in our patient groups with milder disease, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to know that a similar OEF increase has also been reported in ischemic penumbra in focal cerebral ischemia model. 57 To cope with such an increased energy demand, the cortical tissue would have to struggle with energy production because capillary density is relatively low in the cortical surface region. 50 From a biomechanical point of view, the cortical surface region just beneath the skull might encounter a specific type of injury resulting from cavitation because a shock wave is partly reflected at the interface between the cerebral spinal fluid and the skull.…”
Section: Discussionmentioning
confidence: 99%